(untitled) (American Journal of IR 4.0 and Beyond, 2025)
Artificial intelligence has become a significant tool for completing a wide range of tasks, from simple to complex, though its use is subject to various considerations and preferences. This study explored one aspect of the varied usages of artificial intelligence, the AI-generated text (AIGT) detection. This study used a literature review wherein pertinent studies were gathered and selected to discover potential implications. Research objectives were defined to assess the accuracy and reliability of the AI text detectors and identify which AI detectors were evaluated. Three online databases were used to search for relevant literature, of which 34 articles were finalized. Results show that despite most detectors attaining accuracy above 50%, they are unreliable. Paid tools generally perform better than free ones, but there are concerns about bias against non-native English speakers. These tools also struggle with sophisticated AI content and tricks like paraphrasing, so using them carefully and relying on human judgment is important to avoid unfairly discrediting someone’s work. AI-generated text detection technology still has a lot of room for improvement. Users should not rely completely on these tools but rather cooperate with those tools to better find the true writer of a text. Hence, authorities who use these AI detectors should only partially trust these tools, for they are imperfect and can still make mistakes in their judgment.